2022
DOI: 10.3390/biomedicines10020436
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microbiota-Gut-Brain Axis in Regulating Dopaminergic Signaling

Abstract: Dopamine is a neurotransmitter that plays a critical role both peripherally and centrally in vital functions such as cognition, reward, satiety, voluntary motor movements, pleasure, and motivation. Optimal dopamine bioavailability is essential for normal brain functioning and protection against the development of neurological diseases. Emerging evidence shows that gut microbiota have significant roles in maintaining adequate concentrations of dopamine via intricate, bidirectional communication known as the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 166 publications
2
51
1
Order By: Relevance
“…Dopamine, a major neurotransmitter, plays a critical role in vital functions such as cognition, motivation, and voluntary motor movements both peripherally and centrally. Optimal dopamine bioavailability is essential for normal brain functioning and protection against the development of neurological diseases (142). Levodopa is widely used in the treatment of PD, which can cross the blood-brain barrier and can be transformed into dopamine in the brain, thereby alleviating the symptoms of PD (143).…”
Section: Neurotransmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine, a major neurotransmitter, plays a critical role in vital functions such as cognition, motivation, and voluntary motor movements both peripherally and centrally. Optimal dopamine bioavailability is essential for normal brain functioning and protection against the development of neurological diseases (142). Levodopa is widely used in the treatment of PD, which can cross the blood-brain barrier and can be transformed into dopamine in the brain, thereby alleviating the symptoms of PD (143).…”
Section: Neurotransmittersmentioning
confidence: 99%
“…The gut microbes belonging to the genera of Bacteroides, Prevotella, Bifidobacterium, Lactobacillus, Enterococcus, Clostridium, and Ruminococcus can regulate dopaminergic activity (142). van Kessel et al also demonstrated that the TDC genes (tdc) can be found in more than 50 Enterococcus strains (mainly E. faecalis and E. faecium) and several Staphylococcus and Lactobacillus species, while lower plasma levels of levodopa in rats treated with levodopa/carbidopa correlated with the level of bacterial tdc in the jejunum (147).…”
Section: Neurotransmittersmentioning
confidence: 99%
“…RYGB surgery also increases levels of ghrelin and GLP-1, which have been positively associated with obesity, dietary interventions, and dopamine production [ 182 ]. The specific mechanisms on how the complex microbiota and/or the abundance or absence of single bacterial strains impact the dopaminergic system in the gut and the brain have been recently reviewed elsewhere [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dopaminergic system, in particular, plays a significant role in regulating satiety, food-seeking behaviors, and the motivational drive to eat [ 25 , 26 ]. It is also known that gut microbiota plays significant roles in modulating processes that influence dopamine bioavailability via gut-brain signaling [ 14 ]. Different dietary patterns, such as increased intake of animal meat or protein and plant-based carbohydrates, influence the composition of gut microbiota.…”
Section: Changes In Nutrients Dopamine and Microbiotamentioning
confidence: 99%
See 1 more Smart Citation